Criminology aspects of fight against economic criminality (Journal of actual problems of jurisprudence, 2018)
His article deals with the study of criminological aspects of illegal business, as a form of economic crime, aswell as a brief criminological analysis for combating economic crime in the Republic of Kazakhstan. Todayone of the most pressing problems is to ensure the economic security of the state. One of the trends on thematter is to combat illegal business. Sharpened, the crime situation in the economy, said the need to improveefficiency in the fight against economic crime, in particular illegal business.Keywords: economic crime, economic security, criminological aspects, the fight against economic crime.